2012
DOI: 10.1073/pnas.1120811109
|View full text |Cite
|
Sign up to set email alerts
|

Combined linkage and association mapping revealsCYCD5;1as a quantitative trait gene for endoreduplication inArabidopsis

Abstract: Endoreduplication is the process where a cell replicates its genome without mitosis and cytokinesis, often followed by cell differentiation. This alternative cell cycle results in various levels of endoploidy, reaching 4× or higher one haploid set of chromosomes. Endoreduplication is found in animals and is widespread in plants, where it plays a major role in cellular differentiation and plant development. Here, we show that variation in endoreduplication between Arabidopsis thaliana accessions Columbia-0 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 58 publications
(68 reference statements)
0
53
0
Order By: Relevance
“…The currently available large populations, dense genotyping, and the advantage of homozygous lines in the mainly self-fertilizing species Arabidopsis, ought to greatly enhance the power of such studies. Indeed, GWA studies confirmed many of the previously identified genes in experimental mapping populations and mutant studies and detected a number of, to our knowledge, novel candidate genes, although this is limited for quantitative traits (Atwell et al, 2010;Brachi et al, 2010;Li et al, 2010;Todesco et al, 2010;Chan et al, 2011;Chao et al, 2012;Filiault and Maloof, 2012;Sterken et al, 2012;Yano et al, 2013;Chao et al, 2014;Meijón et al, 2014;Bac-Molenaar et al, 2015). Similar to the problem of missing heritability in human GWA studies, where individual variants cannot explain the phenotypic variation despite high heritabilities (Yang et al, 2010;Gibson, 2011;Makowsky et al, 2011), genetic variants cannot fully explain the high heritabilities in plant studies (Brachi et al, 2010;Sasaki et al, 2015).…”
mentioning
confidence: 55%
“…The currently available large populations, dense genotyping, and the advantage of homozygous lines in the mainly self-fertilizing species Arabidopsis, ought to greatly enhance the power of such studies. Indeed, GWA studies confirmed many of the previously identified genes in experimental mapping populations and mutant studies and detected a number of, to our knowledge, novel candidate genes, although this is limited for quantitative traits (Atwell et al, 2010;Brachi et al, 2010;Li et al, 2010;Todesco et al, 2010;Chan et al, 2011;Chao et al, 2012;Filiault and Maloof, 2012;Sterken et al, 2012;Yano et al, 2013;Chao et al, 2014;Meijón et al, 2014;Bac-Molenaar et al, 2015). Similar to the problem of missing heritability in human GWA studies, where individual variants cannot explain the phenotypic variation despite high heritabilities (Yang et al, 2010;Gibson, 2011;Makowsky et al, 2011), genetic variants cannot fully explain the high heritabilities in plant studies (Brachi et al, 2010;Sasaki et al, 2015).…”
mentioning
confidence: 55%
“…Given that the DNA-damaging chemical, zeocin, phenocopies these phenotypes, it is thought that the DNA damage promotes the endocycle and accompanied cell expansion. To examine whether the high-ploidy phenotypes of fas1 are induced through the ATM-dependent DNA damage response, we performed flow cytometry analysis using fully mature leaves and calculated the endoreduplication index (Sterken et al, 2012). The nuclear ploidy levels of cells in first leaves of 21-d-old wildtype plants range from 2C to 32C, indicating that many cells in wild-type leaves have undergone several rounds of endocycles (Fig.…”
Section: The Atm Mutation Partially Restores the Cell Cycle Delay In mentioning
confidence: 99%
“…At least 7,000 nuclei isolated from the first pair of leaves were used for each ploidy measurement. Endoreduplication index (EI) was calculated as EI = (0 3 %2C) + (1 3 %4C) + (2 3 %8C) + (3 3 %16C) + (4 3 %32C) (Sterken et al, 2012) and averaged over at least three technical replicates.…”
Section: Ploidy Measurementsmentioning
confidence: 99%
“…Although length, width, and the dimensions of leaves are important, natural variation in leaf morphology is immense, and methods to quantify the entirety of shape variance are required to determine the full complement of genes regulating differences in populations (Langlade et al, 2005;Chitwood et al, 2012bChitwood et al, , 2012cChitwood et al, , 2012d. Ultimately, the morphology of leaves is determined at the cellular level, and the genetics underlying natural variation in cellular traits are only now beginning to be examined (Massonnet et al, 2011;Sterken et al, 2012).…”
Section: Introductionmentioning
confidence: 99%